Paul’s Teaching on Solidarity With the Weak (Romans 15:1-6) and Its Relevance to Africa (Hekima Review, 2008)
Is the Christian message proclaimed by Paul ‘good news’ to Africa at all? This article highlights the relevance of Paul’s concept of ‘solidarity with the weak’ to the African context characterised by deep divisions between the powerful and the powerless.The author proposes ‘option for the poor’ as a Christian response to the existing power imbalances in politics and economics in Africa.